Incorporating Stud Attachments in the Bar Design for an Implant-Supported Overdenture - Dimokritos Papalexopoulos; Christos Partalis; Panagiotis Lampropoulos; Ioli-Ioanna Artopoulou; Nikitas Sykaras (Hindawi Limited, 2024)
Bone resorption following tooth loss might compromise retention, stability, and support of conventional removable prostheses, and for this reason, implant-supported overdentures are suggested as a viable alternative for completely edentulous patients. Bars, telescopic attachments, or stud attachments have been used to provide retention through a different mechanism of action based on specific design characteristics. The purpose of this report is to thoroughly describe the applied protocol for the fabrication of an implant overdenture supported by two bars incorporating stud attachments. A 67-year-old male patient presented to the Postgraduate Clinic of the National and Kapodistrian University in Athens seeking dental rehabilitation. The remaining teeth were characterized with poor prognosis, mainly due to their periodontal status. The proposed treatment plan included the placement of four implants in the maxilla and two implants in the mandible and the fabrication of implant-supported overdentures. The diagnostic stages revealed adequate prosthetic space that would enable the fabrication of a bar substructure for the maxillary overdenture. To combine the benefits of bars and stud attachments, two bars with four attachments were fabricated. Evaluation of the delivered prosthesis revealed adequate retention, support, and stability achieved with minimal palatal coverage. Patient's reported satisfaction and quality of life were increased. Recall appointments at one, six, and twelve months did not reveal any adverse effects or patient's complaints. According to the present case report, different types of attachments may be used after careful study of each case. More studies are needed to report on different aspects of the chosen treatment plan.